2021
DOI: 10.1111/pere.12400
|View full text |Cite
|
Sign up to set email alerts
|

Relationship form and function: Exploring meaning‐making in young adults' romantic histories

Abstract: Forming stable, supportive romantic relationships is an important determinant of well‐being for adults. Yet, there has been limited research about if and how prior romantic experiences help individuals develop the capacity to enter into such unions. Using grounded theory methods, relationship history interviews were conducted with 35 young adults who provided data about 256 romantic and sexual relationships. The different relationship forms (e.g., hooking up, casual dating, committed partnering) were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…College students who did not have romantic or sexual partners as the COVID-19 pandemic was unfolding may have also experienced unwanted changes to their romantic and sexual lives. For example, college is often seen as an important time for romantic and sexual exploration (Arnett, 2015 ; Jamison & Sanner, 2021 ). As campus was closed and many students moved back to their hometowns, single students may have lost opportunities to meet potential romantic and sexual partners and engage in romantic activities like dating.…”
Section: Introductionmentioning
confidence: 99%
“…College students who did not have romantic or sexual partners as the COVID-19 pandemic was unfolding may have also experienced unwanted changes to their romantic and sexual lives. For example, college is often seen as an important time for romantic and sexual exploration (Arnett, 2015 ; Jamison & Sanner, 2021 ). As campus was closed and many students moved back to their hometowns, single students may have lost opportunities to meet potential romantic and sexual partners and engage in romantic activities like dating.…”
Section: Introductionmentioning
confidence: 99%
“…There are several limitations to this study. First, the current analysis is limited to housework behavior and cannot address how people's perceptions of fairness or expectations from their new partners have changed upon repartnering (Jamison & Sanner, 2021; Pyke & Coltrane, 1996). Moreover, this study cannot address to what extent dissatisfaction from housework was a major issue to those who repartnered.…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to leave Chapters 2 and 3 feeling that straight-cisgender men are primarily invested in their own growth and desires even at the expense of female partners. However, my own scholarship suggests that this may not always be the case (e.g., Jamison & Sanner, 2021). In a qualitative study I conducted about young adults' relationship histories, I found that straight, cis-gender men discussed their growth and development through their relationships with women.…”
Section: Intimacy and Intersectionalitymentioning
confidence: 99%
“…Something that resounds throughout this book is the tension between the freedom of choice and the complexities of navigating those choices. As social norms for forming relationships have become more flexible (Olmstead, 2020) and new policies have paved the way for same‐sex partners to marry (Ogolsky et al, 2019), individuals have been tasked with creating a romantic life that suits their individual needs and desires (Jamison & Sanner, 2021). Although the freedom to make these choices is valuable, it is evident from Dalessandro's stories that individuals continue to struggle with the complexity of these choices, especially as they relate to race, class, and gender.…”
Section: Qualitative Inquiry and Relationship Sciencementioning
confidence: 99%